Analysis The Implementation of Healthy Canteens Elementary Schools in The Working Area Paal V Health Center, Jambi City - Presca Irsita Utami; Puspita Sari; Rizalia Wardiah; M.Ridwan; Oka Lesmas L (International Journal of Health and Medicine, 2025)
Background: Every child has the right to receive education in a healthy environment in accordance with the 1945 Constitution Article 31 paragraph 1. The health of the school environment, especially the existence of a healthy canteen, is an important component in supporting student growth and development. This study aims to analyze the implementation of healthy canteens in elementary schools in the working area of the Paal V Health Center in Jambi City. Methods: This study is a qualitative study with an analytical descriptive approach. Research data was collected through in-depth interviews, FGDs, observations, and documentation, with informants consisting of school principals, health center staff, teachers, canteen sellers, and students. Results: At SDN 64/IV Jambi City, there is a written policy regarding school healthy canteens. The average canteen handler has used an apron as personal protective equipment (PPE) and maintained hand and clothing hygiene. School canteen facilities are equipped with adequate lighting and the availability of clean water. However, it is still found that plastic containers are used for food containers. The informants agreed that the existence of healthy canteens in schools is very important and suggested that canteens only sell food that is filling and free from harmful chemicals. Conclusion: Schools with higher accreditation have better canteen management than schools with lower accreditation, especially in policies, facilities, and supervision.